A high-temperature titanium alloy for long-term use in an extreme environment with high temperature, high pressure and high rotation speed

CN119242984BActive Publication Date: 2026-10-09AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411283672.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2026-10-09
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

[0005]鉴于上述的分析,本发明实施例旨在提供一种高温高压高转速极端环境下长期使用的高温钛合金,用以解决现有技术中航空发动机钛合金零件不能长时间服役于高温(650℃-700℃)高压高转速极端工作环境的问题

Benefits of technology

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242984B_ABST
    Figure CN119242984B_ABST
Patent Text Reader

Abstract

The application relates to a high-temperature titanium alloy for long-term use in an extreme environment with high temperature, high pressure and high rotating speed, and belongs to the technical field of metal materials, solving the problem that titanium alloy parts cannot be used in an extreme working environment with high temperature (650 DEG C-700 DEG C), high pressure and high rotating speed for a long time. The chemical composition of the high-temperature titanium alloy is as follows in percentage by weight: Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-7.0%, Hf: 0.5%-1.5%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.40%-0.90%, W: 0.4%-1.0%, C: 0.05%-0.07%, and Ti: the balance. Through regulation and control of the alloy element composition and content ratio, in combination with a machining process and a heat treatment process, the titanium alloy of the application has excellent strength, creep resistance and anti-over-rotation rupture performance at a high temperature of 650 DEG C-700 DEG C, is suitable for long-term use in an extreme environment with high temperature, high pressure and high rotating speed, and meets the requirements of a new generation of aero-engine titanium alloy parts in a limit high-temperature working state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal materials technology, and in particular to a high-temperature titanium alloy that can be used for a long time under extreme conditions of high temperature, high pressure, and high speed. Background Technology

[0002] Advanced aero-engines are constantly evolving towards higher turbine inlet temperatures, higher thrust-to-weight ratios, and higher pressure ratios, primarily achieved by increasing component working stress, reducing component weight, and improving stiffness. Compared to other commonly used materials, titanium alloys have significant advantages in specific strength, specific stiffness, and specific low-cycle fatigue strength, and also exhibit a significant weight reduction effect. This can significantly improve the engine's thrust-to-weight ratio and service performance, making it the ideal choice for manufacturing aero-engine components.

[0003] Key components of aero-engines, such as bladed disks, blades, and turbine disks, operate under high temperature, high pressure, high load, and multi-load conditions for extended periods. Currently, the maximum long-term service temperature of titanium alloy parts is 500℃~600℃, and the short-term temperature is around 650℃~700℃. The short-term temperature is generally between tens of minutes and a few hours, which represents the extreme high-temperature operating conditions of existing aero-engine titanium alloy parts.

[0004] The new generation of engines operates at higher temperatures and endures more complex and severe stresses, placing more stringent performance requirements on materials. Therefore, there is an urgent need to design a high-temperature titanium alloy that can be used for long-term operation under extreme conditions of high temperature, high pressure, and high speed. Summary of the Invention

[0005] Based on the above analysis, the present invention aims to provide a high-temperature titanium alloy for long-term use in extreme environments of high temperature, high pressure, and high speed, in order to solve the problem that titanium alloy parts for aero-engines cannot be used for long periods of time in extreme working environments of high temperature (650℃-700℃) and high pressure.

[0006] In a first aspect, embodiments of the present invention provide a high-temperature titanium alloy, wherein the chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-7.0%, Hf: 0.5%-1.5%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.40%-0.90%, W: 0.4%-1.0%, C: 0.05%-0.07%, with Ti as the balance.

[0007] Furthermore, in the high-temperature titanium alloy according to claim 1, when Ta ≤ 2.0%, Si ≥ 0.6% in the chemical composition and weight percentage of the high-temperature titanium alloy.

[0008] Furthermore, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-3.5%, Hf: 0.5%-1.0%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.5%-0.9%, W: 0.4%-1.0%, C: 0.05%-0.07%, with Ti as the balance.

[0009] Furthermore, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%, Sn: 3.8%, Zr: 2.5%, Hf: 1%, Mo: 0.30%, Nb: 0.40%, Ta: 2.3%, Si: 0.60%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.

[0010] Furthermore, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.

[0011] Furthermore, the R of the high-temperature titanium alloy at 25°C m ≥1000MPa, R p0.2 ≥900MPa, A5≥6%; R at 650℃ m ≥610MPa, R p0.2 ≥500MPa; creep residual strain ≤0.18% under test conditions of 650℃ temperature, 120MPa creep stress, and 100h time; R at 700℃ m ≥560MPa, R p0.2 The creep residual strain is ≤0.18% under the following test conditions: ≥450MPa; temperature 700℃; creep stress 70MPa; time 100h.

[0012] Secondly, embodiments of the present invention provide a method for preparing the above-mentioned high-temperature titanium alloy, the method comprising:

[0013] (1) Weigh the metal and / or intermediate alloy according to the chemical composition and weight percentage of the high-temperature titanium alloy, melt it, and obtain a titanium alloy ingot.

[0014] (2) The titanium alloy ingot is forged and deformed to obtain a forging blank;

[0015] (3) The forging blank is subjected to solution heat treatment and aging heat treatment in sequence to obtain the high temperature titanium alloy.

[0016] Furthermore, in step (2), the forging deformation specifically includes a first-stage upsetting and drawing, a first heat treatment, and a first-stage upsetting and drawing. The first-stage upsetting and drawing includes three-stage upsetting and drawing, specifically: the titanium alloy ingot is subjected to one-stage upsetting and drawing deformation at temperatures of 1150℃~1400℃, 1100℃~1300℃, and 1000℃~1100℃ respectively, with the deformation amount controlled at 40%-50%.

[0017] Furthermore, in step (3), the temperature of the solution heat treatment is T. β -25℃~T β -10℃, for 1-3 hours;

[0018] Furthermore, the aging heat treatment is performed at a temperature of 700℃-800℃ for a time of 4-7 hours.

[0019] Thirdly, embodiments of the present invention provide an application of the above-mentioned high-temperature titanium alloy in the manufacturing of aero-engine parts, wherein the aero-engine parts are bladed disks, blades, turbine disks, etc.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] 1. The element Hf in the high-temperature titanium alloy of this invention improves the alloy's oxidation resistance and creep resistance at high temperatures; element Zr has a strong high-temperature strengthening effect, and the composite strengthening effect formed with element Sn is higher than that of a single element. It can also refine the silicides in the alloy and promote the dispersed distribution of silicides, hindering the growth of the original β grains, thereby obtaining a fine lamellar structure, achieving the effect of improving creep performance without reducing the plasticity of the alloy.

[0022] Increasing the Ta content can improve the creep performance of the alloy and also enhance its oxidation resistance; the solid solution strengthening and precipitation strengthening effects of Si can significantly improve the high-temperature creep performance of the alloy.

[0023] The element W in the alloy can form composite phases with titanium, such as β1(Ti,W) titanium-rich phase and β2(Ti,W) tungsten-rich phase, which can improve the density and mechanical properties of the alloy.

[0024] By controlling the composition and content ratio of alloying elements, titanium alloys can exhibit excellent strength, creep resistance, and over-rotation fracture resistance at high temperatures of 650℃-700℃, making them suitable for long-term use in extreme environments of high temperature, high pressure, and high speed, thus meeting the requirements of the extreme high-temperature working conditions of titanium alloy parts (integral bladed disks) for next-generation aero-engines.

[0025] 2. Existing titanium alloys have a low Si content (less than 0.6%) to avoid excessive Si content leading to the formation of too many subcrystalline α phases and insufficient toughness. Unlike existing titanium alloys, this invention improves creep performance by increasing Si content while maintaining a relatively high Ta content. However, excessive Si content can reduce plasticity and creep performance due to uneven precipitation of silicide phases. Therefore, Zr is added to the alloy to promote the dispersed distribution of silicide phases, ensuring that even with a higher Si content (0.9%), defects such as segregation do not occur, resulting in a more uniform alloy composition (e.g., ...). Figure 2 (As shown).

[0026] 3. The element W in the high-temperature titanium alloy of the present invention can refine the grain structure of the titanium alloy and improve the high-temperature strength and creep resistance of the titanium alloy, which is crucial for titanium alloy parts that work under high temperature conditions for a long time. However, excessive addition of tungsten may also lead to segregation and embrittlement of the structure, resulting in a decrease in the creep resistance of the alloy. The content of W in the high-temperature alloy of the present invention is controlled at 0.4%-1.0%.

[0027] 4. This invention adjusts the composition and content of the high-temperature titanium alloy to achieve high tensile strength (≥610MPa) and yield strength (≥500MPa) at 650℃, adapting to the high-temperature working environment of 650℃. Furthermore, it exhibits good creep resistance under high temperature (650℃) and high creep stress (120MPa), with residual creep strain ≤0.18% after 100 hours of testing. At 700℃, it still possesses high tensile strength (≥560MPa) and yield strength (≥450MPa), adapting to extreme high-temperature working environments. Moreover, under high temperature (700℃) and high creep stress (70MPa), it still exhibits good creep resistance, with residual creep strain ≤0.18% after 100 hours of testing. This high-temperature titanium alloy is suitable for manufacturing parts operating at extreme high temperatures, such as aero-engine parts operating for extended periods under extreme high-temperature, high-pressure, and high-speed environments, promoting the development and progress of aerospace.

[0028] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description

[0029] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.

[0030] Figure 1 The microstructure of the high-temperature titanium alloy forging 1 obtained in Example 1 is shown in the image.

[0031] Figure 2 The image shows the microstructure of the high-temperature titanium alloy forging 2 obtained in Example 2.

[0032] Figure 3 The image shows the microstructure of the high-temperature titanium alloy forging 3 obtained in Example 3.

[0033] Figure 4 The image shows the microstructure of the high-temperature titanium alloy forging 4 obtained in Example 4.

[0034] Figure 5 The image shows the microstructure of the high-temperature titanium alloy forging 5 obtained in Example 5.

[0035] Figure 6 Overrun test curve of the integral bladed disk made of high-temperature titanium alloy forging 1 under 650℃ / 115% conditions;

[0036] Figure 7 Overrun test curve of the integral bladed disk made of high-temperature titanium alloy forging 1 under 650℃ / 122% conditions;

[0037] Figure 8 The overrun test curve of the integral bladed disk made of high-temperature titanium alloy forging 1 under the condition of 650℃ / 150%. Detailed Implementation

[0038] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0039] Key components of aero-engines, such as bladed disks and blades, operate under conditions of high temperature, high pressure, high load, and multiple loads for extended periods. Currently, the maximum long-term service temperature for titanium alloy parts is 500℃~600℃, with short-term temperatures reaching approximately 650℃~700℃, typically lasting from tens of minutes to several hours. This represents the extreme high-temperature operating conditions for existing aero-engine titanium alloy parts. Next-generation engines will operate at even higher temperatures and endure more complex and severe stresses, placing even more stringent performance requirements on materials.

[0040] Therefore, the present invention provides a high-temperature titanium alloy, wherein the chemical composition and weight percentage of the high-temperature titanium alloy are Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-7.0%, Hf: 0.5%-1.5%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.40%-0.90%, W: 0.4%-1.0%, C: 0.05%-0.07%, and Ti as the balance.

[0041] The following details the function and dosage selection of the components contained in this invention:

[0042] Al (Al) has a significant solid solution strengthening effect, which can improve the mechanical properties of the alloy, especially enabling it to withstand greater stress and load at high temperatures; it also improves oxidation resistance; increases the phase transformation temperature, which helps maintain the microstructure stability at high temperatures, thereby extending its service life; and improves thermal strength, allowing the alloy to maintain its strength at high temperatures. An Al content above 6.0% is to ensure the alloy's room temperature, high temperature strength, and thermal strength. However, if the Al content exceeds 8.0%, excessive α2 phase will precipitate during use, reducing the alloy's thermal stability, plasticity, toughness, and processing performance.

[0043] Sn: It enhances the strength of the alloy through solid solution strengthening; it also improves heat resistance, i.e., maintaining high strength at high temperatures; controlling the content above 2.5% is to achieve higher room temperature strength and high temperature strength. Excessive Sn content (greater than 4.5%) may form ordered phases (such as Ti3Sn), reducing the plasticity and thermal stability of the alloy.

[0044] Mo (Mo): Mo enhances the strength of alloys through solid solution strengthening and has a significant impact on their thermal stability and creep properties. The addition of Mo improves the high-temperature rupture and creep resistance of alloys, allowing them to maintain high strength and stability even at high temperatures. It also improves machinability (reducing the tendency for forging cracks) and works synergistically with other alloying elements (such as Al, Sn, and Zr) to produce more complex and stable β-phase structures with a body-centered cubic (bcc) structure at higher temperatures, thereby increasing the alloy's strength and heat resistance. Excessive Mo content (above 0.85%) not only inhibits silicide precipitation and reduces creep properties but also reduces plasticity, increases the alloy's resistance to deformation and its tendency to hot crack, making machining more difficult. Without Mo and W, the tensile strength of the alloy will decrease drastically when the service temperature reaches above 600℃.

[0045] Nitrogen (Nb): Enhances alloy strength through solid solution strengthening, improves hot strength and creep resistance. In synergy with other alloying elements (such as Al, Sn, and Zr), it can produce more complex and stable phase structures, including solid solutions, intermetallic compounds (titanium-aluminum-niobium W phase), and complex precipitates, thereby improving the alloy's strength and heat resistance. Excessive Nb content (above 0.8%) can easily lead to compositional segregation, reduce plasticity, increase alloy deformation resistance and hot cracking tendency, making processing more difficult.

[0046] C: Excessive C content will cause carbide precipitation, reducing the alloy's plasticity and toughness, and worsening its processing performance; it will also reduce high-temperature creep performance (carbide will become the starting point and path for creep crack propagation). Adding a small amount of C is to broaden the processing window.

[0047] Zr: Zr has a strong high-temperature strengthening effect. When combined with Sn, the strengthening effect is greater than that of a single element. It can also refine silicides in the alloy and promote their dispersed distribution, hindering the growth of the original β grains, thereby obtaining a fine lamellar structure with an average interlamellar spacing of 0.25-0.30 μm. This achieves the effect of improving creep performance without reducing the plasticity of the alloy. However, excessive Zr content will reduce the solubility of Si, thus affecting the precipitation behavior and properties of the alloy. Therefore, this invention controls the Zr content in the alloy to 2.5%-7.0%, and more preferably 2.5%-3.5%.

[0048] Hf: Hf improves the alloy's oxidation resistance and creep resistance at high temperatures. Hf works synergistically with other alloying elements to produce a more complex and stable phase structure, thereby improving the alloy's heat resistance. However, if the content is too high, it is prone to segregation, which will reduce high-temperature strength, room temperature plasticity and high-temperature plasticity are significantly reduced, and it is expensive. Therefore, the content should not be too high, which is 0.5%-1.5%, preferably 0.5%-1.0%.

[0049] Ta: Ta forms a composite solid solution strengthening with W, which improves the high-temperature tensile strength. Increasing the Ta content can improve the creep performance of the alloy and also improve the oxidation resistance of the material. However, if the Ta content is too high, it will not significantly improve the creep performance and oxidation resistance of the material, and will also reduce the plasticity of the alloy, increase the cost and processing difficulty. The Ta content of this invention is 1.0%-3.0%.

[0050] Si: When the Ta content cannot be too high, increasing the Si content can ensure the improvement of the alloy's creep performance. The solid solution strengthening and precipitation strengthening effects of elemental Si can significantly improve the high-temperature creep performance of the alloy. For existing titanium alloys, a Si content greater than 0.6% will reduce the alloy's plasticity and creep performance due to the uneven precipitation of silicide precipitates. In the process of researching titanium alloys, the inventors of this application have found through multiple experiments that, while increasing the Si content to improve the alloy's creep resistance, the addition of elemental Zr can prevent the uneven precipitation of silicide precipitates and promote the dispersed distribution of silicide precipitates, strengthen grain boundaries, and improve the alloy's strength and other properties. After the synergistic effect of high Si content and Zr, the dispersed silicide distribution can hinder dislocation and grain boundary slip, thereby improving creep performance. The Si content of this invention is 0.4%-0.9%, breaking through the upper limit of silicon content in existing titanium alloys.

[0051] W: The element W in the alloy can form composite phases with titanium, such as β1(Ti,W) titanium-rich phase and β2(Ti,W) tungsten-rich phase, which can improve the high-temperature strength and creep resistance of titanium alloys, which is crucial for titanium alloy parts that work under high-temperature conditions for a long time. However, excessive addition of tungsten may also lead to segregation and embrittlement of the microstructure, resulting in a decrease in the creep resistance of the alloy. The content of W in the high-temperature alloy of this invention is controlled at 0.4%-1.0%.

[0052] Specifically, the microstructure of the high-temperature titanium alloy of this invention is a bimodal structure, including an equiaxed α phase and a β-transformation structure. The β-transformation structure contains lamellar β phase and lamellar α phase, the latter also known as secondary α phase. The equiaxed α phase is beneficial to the hardness and strength of the titanium alloy and helps improve its thermal stability, while the β-transformation structure is beneficial to its toughness and plastic deformation capacity. Therefore, the bimodal structure can balance the strength and plasticity of the alloy to a certain extent. By adjusting the composition and proportion of the titanium alloy, the type and parameters of the bimodal structure can be adjusted within a certain range to achieve the optimal matching of the alloy's mechanical properties. This improves the long-term service capability of titanium alloy parts under extreme conditions of high temperature, high pressure, and high speed while ensuring the instantaneous mechanical properties (tensile strength, yield strength) of the titanium alloy under high temperature conditions. In the microstructure of the high-temperature titanium alloy of this invention, the content of the equiaxed α phase is 6%-15%. According to some specific embodiments of this invention, the content of the equiaxed α phase in the microstructure of the high-temperature titanium alloy is 9.74%, 6.4%, 13.80%, 9.34%, or 6.14%, respectively.

[0053] To ensure improved creep performance of the alloy, this invention improves creep performance by increasing Si content when Ta content is low. Specifically, in the chemical composition and weight percentage of the high-temperature titanium alloy, when Ta ≤ 2.0%, Si ≥ 0.6%; when Ta > 2.0%, Si 0.40%-0.90%.

[0054] To further improve the overall performance of the above-mentioned high-temperature titanium alloy, the composition of the above-mentioned high-temperature titanium alloy, by mass percentage, can be: Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-3.5%, Hf: 0.5%-1.0%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.5%-0.9%, W: 0.4%-1.0%, C: 0.05%-0.07%, with the balance being titanium and unavoidable trace impurities.

[0055] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%, Sn: 3.8%, Zr: 2.5%, Hf: 1.0%, Mo: 0.3%, Nb: 0.4%, Ta: 2.3%, Si: 0.6%, W: 0.8%, C: 0.05%-0.07%, Ti: balance.

[0056] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.

[0057] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.0%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.

[0058] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.50%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.

[0059] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 5.9%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.8%, C: 0.05%-0.07%, Ti: balance.

[0060] By controlling the composition and content ratio of alloying elements, not only do they exhibit excellent mechanical properties at room temperature, but specifically, R m ≥1000MPa, R p0.2 ≥900MPa, A5≥6%; and it also exhibits excellent strength and creep resistance at high temperatures of 650-700℃. Specifically, the short-time mechanical properties in an environment of 600℃-700℃ meet the design requirements: under 600℃ conditions, R m ≥700MPa, R p0.2 ≥600MPa; at 650℃, R m ≥610MPa, R p0.2 ≥500MPa; at 700℃, R m ≥560MPa, R p0.2 The creep resistance at ≥450MPa and 600℃-700℃ meets the design requirements. The creep residual strain at 700℃ / 70MPa / 100h is ≤0.18%, at 650℃ / 120MPa / 100h is ≤0.18%, and at 600℃ / 160MPa / 100h is ≤0.12%.

[0061] This invention characterizes the mechanical properties of high-temperature titanium alloy forgings according to testing standards GB / T 228.1, GB / T 228.2 and GB / T 2039, and obtains microstructure photographs of the forgings using a metallographic microscope.

[0062] This invention also provides a method for preparing the above-mentioned high-temperature titanium alloy, comprising smelting, forging, and heat treatment, specifically including:

[0063] (1) Weigh the metal and / or intermediate alloy raw materials according to the chemical composition and weight percentage of the high-temperature titanium alloy, melt them, and obtain titanium alloy ingots.

[0064] (2) The titanium alloy ingot is forged and deformed to obtain a forging blank;

[0065] (3) The forging blank is heat-treated to obtain the high-temperature titanium alloy.

[0066] Specifically, in step (1), the raw materials are pure Al, sponge zirconium, sponge titanium, Ti-Sn, Ti-Hf, Ti-Mo or Al-Mo, Ti-Ta or Al-Ta, Ti-Nb or Al-Nb, Al-Si, Al-W and other intermediate alloys.

[0067] Specifically, in step (1), the melting is vacuum consumable electrode melting. The specific steps are as follows: First, all raw materials except sponge titanium are uniformly mixed using a mixing and spreading machine to obtain mixed raw materials; second, the sponge titanium is uniformly divided into three parts, and the mixed raw materials are divided into two parts, and the sponge titanium, mixed raw materials, mixed raw materials, and sponge titanium are uniformly placed in a mold in the order of sponge titanium, mixed raw materials, sponge titanium, and sponge titanium to be pressed into electrodes, and the electrodes are welded together to obtain consumable electrodes; third, a titanium alloy ingot with uniform composition is obtained through three vacuum consumable melting methods, and shrinkage cavities and surface oxide scale are removed.

[0068] Specifically, in step (2), the forging deformation includes a first stage of upsetting and drawing, a first heat treatment, and a second stage of upsetting and drawing.

[0069] According to a preferred embodiment of the present invention, the first stage of upsetting includes three-stage upsetting, specifically comprising: subjecting the titanium alloy ingot to one to two upsetting deformations at temperatures of 1150℃~1400℃, 1100℃~1300℃, and 1000℃~1100℃, with the deformation amount controlled at 40%-50%; the first upsetting not only breaks up the coarse β grains but also plays a role in uniform annealing, further promoting compositional homogenization. In addition, the gradual decrease in temperature can suppress grain growth during heating in the β region. The temperature of the first upsetting is about 200-250℃ above the phase transformation point because the original ingot grains are coarse and have high deformation resistance. After the first stage of upsetting, the grains break up; the second upsetting has lower deformation resistance than the first, so the deformation temperature is lower, but still needs to be above the phase transformation point. This step is to further refine the grains; similarly, the temperature of the third upsetting is lower than that of the second upsetting.

[0070] According to a preferred embodiment of the present invention, the temperature of the primary heat treatment is T. β +10℃~T β +40℃ to reduce the non-uniformity of the microstructure at the alloy edge and core, and promote the homogenization of the microstructure; the heating time is related to the specifications of the bar or forging being prepared, for example, for a bar with a diameter of 210mm, the holding time is about 240min-300min.

[0071] Specifically, in order to improve the temperature uniformity of the entire forging and avoid problems such as thermal stress, deformation, and cracking caused by directly heating to the heat treatment temperature, the forging needs to be preheated before heat treatment. The preheating temperature is 950℃-980℃.

[0072] According to a preferred embodiment of the present invention, the second stage upsetting is performed at T β -50℃~T βThe alloy undergoes 3 to 10 upsetting and drawing processes at -10℃. The deformation amount in the second stage of upsetting and drawing is 40% to 50%. This process obtains a fine-grained, equiaxed, and uniform microstructure through multiple upsetting and drawing processes, which further promotes the homogenization of the alloy microstructure.

[0073] After the initial upsetting and homogenization heat treatment, the grains have been initially refined, so the deformation temperature can be lowered below the phase transformation point. This stage of deformation aims to further refine the grain size; if the temperature is too high, the grains will grow again. The greater the deformation amount, the better the grain refinement. The deformation amount is related to the alloy's deformation resistance; within the allowable range of deformation resistance, the greater the better. Exceeding 50% may lead to cracking.

[0074] According to a preferred embodiment of the present invention, after the second stage upsetting and drawing, the process further includes: according to the design requirements of the target forging product, at T... β -50℃~T β The forming process is carried out at -10℃ to obtain the target forging blank;

[0075] Preferably, the target forging is an integral bladed disk.

[0076] Forging deformation yields a uniform processed microstructure. Solution aging heat treatment is a comprehensive strengthening process, primarily aimed at improving the strength and creep resistance of titanium alloys while maintaining or improving their plasticity and toughness to achieve excellent comprehensive mechanical properties.

[0077] Specifically, in step (3), the heat treatment includes solution heat treatment and aging heat treatment.

[0078] The purpose of solution heat treatment is to dissolve and precipitate phases to form a homogeneous solid solution. It also reduces stress concentration at grain boundaries and phase boundaries, preparing the alloy for subsequent aging treatment. Furthermore, using optimized water cooling methods can refine the grain structure and improve alloy strength. The goal is to ensure that the phases dissolve and precipitate within the specified time frame of the solution heat treatment.

[0079] The purpose of aging heat treatment is to re-precipitate the strengthening phase uniformly, forming a fine and dispersed distribution of the strengthening phase, thereby improving the alloy's strength, enhancing its structural stability, and reducing structural changes (such as phase transformation and grain growth) during high-temperature or long-term use, thus improving the material's creep resistance and thermal stability. The aging time must ensure the precipitation of the aging phase; if the time is too long, the grains will coarsen; element diffusion and phase transformation will occur, and the structural stability will also deteriorate.

[0080] According to a preferred embodiment of the present invention, the temperature of the solution heat treatment is T. β -25℃~T β -10℃, for 1-3 hours, water cooling or air cooling, preferably water cooling.

[0081] According to a preferred embodiment of the present invention, the aging heat treatment is performed at a temperature of 700-800°C for 4-7 hours, followed by air cooling.

[0082] Solution aging heat treatment combines solution treatment and aging treatment. By dissolving first and then precipitating, the element distribution in the alloy is more uniform, and the precipitated phases are finer and more dispersed. This significantly improves the alloy's hardness, strength, wear resistance and corrosion resistance, while ensuring the alloy's high-temperature creep resistance, good toughness and plasticity.

[0083] Thirdly, embodiments of the present invention provide an application of the above-mentioned high-temperature titanium alloy in aero-engine parts, wherein the aero-engine parts are bladed disks, blades, and turbine disks.

[0084] According to a preferred embodiment of the present invention, the high-temperature titanium alloy of the present invention is applied to the integral bladed disk of an aero-engine. Under high temperature, high pressure and high speed environment, the over-rotation fracture performance of the high-temperature titanium alloy integral bladed disk is tested. It is found that after the over-rotation test at 650°C and 115% speed, no significant change in size and no visible cracks are observed; after the over-rotation test at 122% speed, no significant change in size and no visible cracks are observed; after the over-rotation test at 150% speed, no significant change in size is observed, but the test piece fractures.

[0085] This invention, by adjusting the composition and content of high-temperature titanium alloys and combining them with reasonable preparation processes and parameters, enables high-temperature titanium alloy parts to possess excellent strength, creep resistance, and over-rotation fracture resistance at high temperatures of 650℃-700℃, thus adapting to extreme high-temperature working environments. It provides design material selection for components of advanced aero-engines and other weapon systems operating under extreme service environments such as high temperature, high pressure, and high speed, thereby extending the service life of aero-engines and other equipment in harsh environments.

[0086] The technical solution of the present invention is further demonstrated below through specific embodiments and comparative examples. The preparation methods of the high-temperature titanium alloy ingots in the embodiments and comparative examples are the same, specifically including:

[0087] (1) Weigh the raw materials according to the mass ratio of high temperature titanium alloy, including pure Al, sponge zirconium, intermediate alloys Ti-Sn, Ti-Hf, Ti-Mo, Al-Nb, Ti-Ta, Al-Si and Al-W, carbon powder and sponge titanium, and mix the other raw materials except sponge titanium using a mixing and spreading machine to obtain a mixture.

[0088] (2) The weighed sponge titanium is divided into three equal parts and the mixture is divided into two equal parts. The sponge titanium, mixture, sponge titanium, mixture and sponge titanium are placed in the mold in sequence and pressed into electrodes. The electrodes are then welded together to obtain consumable electrodes. A high-temperature titanium alloy ingot with uniform composition is obtained by three vacuum consumable melting methods, and shrinkage cavities and surface oxide scale are removed.

[0089] The following examples and comparative examples demonstrate the processing and heat treatment of specific high-temperature titanium alloy ingots, the mechanical properties of the forgings obtained by testing according to standards GB / T 228.1, GB / T 228.2 and GB / T 2039, and the microstructure photographs of the forgings obtained by metallographic microscopy.

[0090] Example 1

[0091] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 1 are as follows: Al: 6.0%, Sn: 3.8%, Zr: 2.5%, Hf: 1.0%, Mo: 0.3%, Nb: 0.4%, Ta: 2.3%, Si: 0.6%, W: 0.8%, C: 0.055%, Ti: balance.

[0092] The steps for machining and heat treating the high-temperature titanium alloy ingot 1 include:

[0093] (1) The high-temperature titanium alloy ingot 1 was subjected to upsetting and drawing deformation at temperatures of 1180℃, 1120℃ and 1030℃ in sequence, with a total deformation of 45%.

[0094] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1045℃, and the heat treatment is carried out in one step: after holding at 950℃ for 180 minutes, the temperature is raised to 1070℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0095] The second stage of upsetting and drawing: eight upsetting and drawing deformations are carried out at a temperature of 1030℃, with a deformation amount of 45%;

[0096] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1025℃, it is held for 2 hours and then air-cooled; at 700℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 1.

[0097] Microstructure photograph of high-temperature titanium alloy forging 1 is shown below. Figure 1 As shown, from Figure 1 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the content of equiaxed α phase is 9.74%, the average size is 4.50 μm, and the average interlamellar spacing is 0.24 μm.

[0098] The mechanical properties of high-temperature titanium alloy forging 1 are shown in Table 1:

[0099] Table 1

[0100]

[0101] Example 2

[0102] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 2 are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.055%, Ti: balance.

[0103] The steps for machining and heat treating the high-temperature titanium alloy ingot 2 include:

[0104] (1) The high-temperature titanium alloy ingot 2 was subjected to two upsetting and drawing deformations at temperatures of 1150℃, 1100℃ and 1000℃ respectively, with a total deformation of 40%.

[0105] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1045℃, and the heat treatment is carried out in one step: after holding at 980℃ for 120 minutes, the temperature is raised to 1085℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0106] The second stage of upsetting and drawing: three upsetting and drawing deformations are carried out at a temperature of 1035℃, with a deformation amount of 50%;

[0107] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1020℃, it is held for 2 hours and then air-cooled; at 800℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 2.

[0108] Microstructure photograph of high-temperature titanium alloy forging 2 as shown in Figure 2 Figure 2 As shown, from Figure 2 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the content of equiaxed α phase is 6.4%, the average size is 3.40 μm, and the average interlamellar spacing is 0.25 μm.

[0109] The mechanical properties of high-temperature titanium alloy forging 2 are shown in Table 2:

[0110] Table 2

[0111]

[0112] Example 3

[0113] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 3 are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.0%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.80%, C: 0.055%, Ti: balance.

[0114] The steps for machining and heat treating the high-temperature titanium alloy ingot 3 include:

[0115] (1) The high-temperature titanium alloy ingot 3 was subjected to upsetting deformation once at temperatures of 1400℃, 1300℃ and 1100℃, with a total deformation of 50%.

[0116] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1052℃, and the heat treatment is carried out in one step: after holding at 950℃ for 120 minutes, the temperature is raised to 1062℃ and held for 180 minutes, and then the furnace is removed and air-cooled.

[0117] The second stage of upsetting and drawing: 10 upsetting and drawing deformations are carried out at a temperature of 1005℃, with a deformation amount of 45%;

[0118] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1040℃, it is held for 2 hours and then air-cooled; at 750℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 3.

[0119] Microstructure photograph of high-temperature titanium alloy forging 3 as shown in Figure 3 Figure 3 As shown, from Figure 3 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the content of equiaxed α phase is 11.44%, the average size is 4.23 μm, and the average interlamellar spacing is 0.28 μm.

[0120] The mechanical properties of high-temperature titanium alloy forging 3 are shown in Table 3:

[0121] Table 3

[0122]

[0123] Example 4

[0124] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 4 are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.50%, W: 0.80%, C: 0.055%, Ti: balance.

[0125] The steps for machining and heat treating the high-temperature titanium alloy ingot 4 include:

[0126] (1) The high-temperature titanium alloy ingot 3 was subjected to upsetting deformation once at temperatures of 1180℃, 1120℃ and 1030℃ respectively, with a total deformation of 40%.

[0127] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1040℃, and the heat treatment is carried out in one step: after holding at 950℃ for 180 minutes, the temperature is raised to 1060℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0128] The second stage of upsetting and drawing: eight upsetting and drawing deformations are carried out at a temperature of 1030℃, with a deformation amount of 45%;

[0129] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1020℃, it is held for 2 hours and then air-cooled; at 700℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 4.

[0130] Microstructure photograph of high-temperature titanium alloy forging 4 is shown below. Figure 4 As shown, from Figure 4 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the equiaxed α phase content is 9.34%, the average size is 4.82 μm, and the average interlamellar spacing is 0.29 μm. Mechanical properties are shown in Table 4.

[0131] Table 4

[0132]

[0133] Example 5

[0134] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 5 are as follows: Al: 5.9%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2%, Si: 0.70%, W: 0.80%, C: 0.055%, Ti: balance.

[0135] The steps for machining and heat treating the high-temperature titanium alloy ingot 5 include:

[0136] (1) The high-temperature titanium alloy ingot 5 was subjected to upsetting and drawing deformation at temperatures of 1180℃, 1120℃ and 1030℃ in sequence, with a total deformation of 45%.

[0137] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1040℃, and the heat treatment is carried out in one step: after holding at 950℃ for 180 minutes, the temperature is raised to 1065℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0138] The second stage of upsetting and drawing: eight upsetting and drawing deformations are carried out at a temperature of 1030℃, with a deformation amount of 45%;

[0139] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1020℃, it is held for 2 hours and then air-cooled; at 700℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 5.

[0140] Microstructure photograph of high-temperature titanium alloy forging 5 is shown below. Figure 5 As shown, from Figure 5 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the equiaxed α phase content is 6.14%, the average size is 3.39 μm, and the average interlamellar spacing is 0.23 μm. Mechanical properties are shown in Table 5.

[0141] Table 5

[0142]

[0143] Comparative Example 1

[0144] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 6 are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.50%, W: 1.2%, C: 0.055%, Ti: balance.

[0145] The steps for machining and heat treating the high-temperature titanium alloy ingot 6 include:

[0146] (1) The high-temperature titanium alloy ingot 6 was subjected to one stage of upsetting and drawing deformation at temperatures of 1180℃, 1120℃ and 1030℃, with a deformation amount of 45%.

[0147] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1040℃, and the heat treatment is carried out in one step: after holding at 950℃ for 180 minutes, the temperature is raised to 1065℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0148] The second stage of upsetting and drawing: eight upsetting and drawing deformations are carried out at a temperature of 1030℃, with a deformation amount of 45%;

[0149] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1020℃, it is held for 2 hours and then air-cooled; at 700℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 6.

[0150] The mechanical properties of high-temperature titanium alloy forging 6 are shown in Table 6:

[0151] Table 6

[0152]

[0153] Comparative Example 2

[0154] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 7 are as follows: Al: 5.9%, Sn: 4.0%, Zr: 3.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2%, Si: 0.40%, W: 0.8%, C: 0.055%, Ti: balance.

[0155] The steps for machining and heat treating the high-temperature titanium alloy ingot 7 include:

[0156] (1) The high-temperature titanium alloy ingot 7 was subjected to one stage of upsetting and drawing deformation at temperatures of 1180℃, 1120℃ and 1030℃, with a deformation amount of 45%.

[0157] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1040℃, and the heat treatment is carried out in one step: after holding at 950℃ for 180 minutes, the temperature is raised to 1065℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0158] The second stage of upsetting and drawing: eight upsetting and drawing deformations are carried out at a temperature of 1030℃, with a deformation amount of 45%;

[0159] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1020℃, it is held for 2 hours and then air-cooled; at 700℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 7.

[0160] The mechanical properties of high-temperature titanium alloy forging 7 are shown in Table 7:

[0161] Table 7

[0162]

[0163] Comparative Example 3

[0164] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 8 are as follows: Al: 6.0%, Sn: 4.0%, Hf: 3.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.40%, W: 0.8%, C: 0.055%, Ti: balance.

[0165] The steps for machining and heat treating the high-temperature titanium alloy ingot 8 include:

[0166] (1) The high-temperature titanium alloy ingot 8 was subjected to one stage of upsetting and drawing deformation at temperatures of 1180℃, 1120℃ and 1030℃, with a deformation amount of 45%.

[0167] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... βThe temperature is 1040℃, and the heat treatment is carried out in one step: after holding at 950℃ for 180 minutes, the temperature is raised to 1065℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0168] The second stage of upsetting and drawing: eight upsetting and drawing deformations are carried out at a temperature of 1030℃, with a deformation amount of 45%;

[0169] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1020℃, it is held for 2 hours and then air-cooled; at 700℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 8.

[0170] The mechanical properties of high-temperature titanium alloy forging 8 are shown in Table 8:

[0171] Table 8

[0172]

[0173] Comparative Example 4

[0174] When Ta ≤ 2.0% and Si < 0.6%, and the contents of other components are within the specified range, the microstructure and properties of the alloy demonstrate the synergistic effect of the two on the creep properties of the alloy.

[0175] The chemical composition and weight percentage of the high-temperature titanium alloy ingot 9 are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1%, Si: 0.50%, W: 0.8%, C: 0.055%, Ti: balance.

[0176] The steps for machining and heat treating the high-temperature titanium alloy ingot 9 include:

[0177] (1) The high-temperature titanium alloy ingot 9 was subjected to one stage of upsetting and drawing deformation at temperatures of 1180℃, 1120℃ and 1030℃, with a deformation amount of 45%.

[0178] Measurements showed that the T0 of the titanium alloy after the first stage of upsetting and drawing was... β The temperature is 1040℃, and the heat treatment is carried out in one step: after holding at 950℃ for 180 minutes, the temperature is raised to 1065℃ and held for 120 minutes, and then the furnace is removed and air-cooled.

[0179] The second stage of upsetting and drawing: eight upsetting and drawing deformations are carried out at a temperature of 1030℃, with a deformation amount of 45%;

[0180] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at 1020℃, it is held for 2 hours and then air-cooled; at 700℃, it is held for 5 hours and then air-cooled to obtain high-temperature titanium alloy forging 9.

[0181] The mechanical properties of high-temperature titanium alloy forging 9 are shown in Table 9:

[0182] Table 9

[0183]

[0184] Performance testing

[0185] The high-temperature titanium alloys in the examples and comparative examples were formed at the temperature of their respective second-stage upsetting to prepare integral bladed disk forgings; wherein the outline dimensions of the integral bladed disk forgings were 210mm in diameter and 50mm in diameter, and the integral bladed disk parts were obtained after machining.

[0186] The over-rotation fracture test method was used to test the over-rotation fracture performance of the integral bladed disk assembly under high temperature, high pressure, and high speed conditions. The test curves for the over-rotation fracture performance of the integral bladed disk component made of high-temperature titanium alloy 1 are shown below. Figure 6-8 As shown in the figure. The test results show that, when the integral bladed disk part made of high-temperature titanium alloy 1 was at a temperature of 650℃ and rotation speeds of 115% and 122% respectively, after rotation times of 520s and 530s, the dimensions of the integral bladed disk part did not show significant changes, and no cracks were observed. However, when the temperature was 650℃ and the rotation speed was 150%, after rotation time of 675s, the dimensions of the integral bladed disk part did not show significant changes, and the test piece cracked.

[0187] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A high-temperature titanium alloy, characterized in that, The chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-7.0%, Hf: 0.5%-1.5%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-2.0%, Si: 0.60%-0.90%, W: 0.8%-1.0%, C: 0.05%-0.07%, Ti balance; The microstructure of the high-temperature titanium alloy is a bimodal structure, including an equiaxed α phase and a β transformation structure. The β transformation structure contains lamellar β phase and lamellar α phase, and the content of the equiaxed α phase is 6.14%-9.74%. The high-temperature titanium alloy at 25°C R m ≥1000MPa, R p0.2 ≥900MPa, A5 is 6%~11.7%; R at 650℃ m ≥610MPa, R p0.2 ≥500MPa; creep residual strain of 0.12%~0.18% under test conditions of 650℃ temperature, 120MPa creep stress, and 100h time; R at 700℃ m ≥560MPa, R p0.2 The creep residual strain is ≤0.18% under the following test conditions: ≥450MPa; temperature 700℃; creep stress 70MPa; time 100h.

2. The high-temperature titanium alloy according to claim 1, characterized in that, The chemical composition and weight percentage of the high-temperature titanium alloy are Al: 6.0%, Sn: 4.0%, Zr: 3.0%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.80%, C: 0.05%-0.07%, Ti balance.

3. The high-temperature titanium alloy according to claim 1, characterized in that, The chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 5.9%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.8%, C: 0.05%-0.07%, Ti: balance.

4. The high-temperature titanium alloy according to claim 1, characterized in that, The chemical composition and weight percentage of the high-temperature titanium alloy are as follows: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.

5. A method for preparing the high-temperature titanium alloy according to any one of claims 1-4, characterized in that, The method includes: (1) Weigh the metal and / or master alloy according to the chemical composition and weight percentage of the high-temperature titanium alloy, melt it, and obtain a titanium alloy ingot; (2) The titanium alloy ingot is forged and deformed to obtain a forging blank; (3) The forging blank is subjected to solution heat treatment and aging heat treatment in sequence to obtain the high temperature titanium alloy.

6. The method according to claim 5, characterized in that, In step (2), the forging deformation specifically includes a first stage upsetting and drawing, a first heat treatment, and a second stage upsetting and drawing. The first stage upsetting and drawing includes three-stage upsetting and drawing, specifically: the titanium alloy ingot is subjected to one-stage upsetting and drawing deformation at temperatures of 1150℃~1400℃, 1100℃~1300℃, and 1000℃~1100℃ respectively, with the deformation amount controlled at 40%-50%.

7. The method according to claim 5, characterized in that, In step (3), the temperature of the solution heat treatment is T. β -25℃~T β -10℃, for 1-3 hours; And / or, the aging heat treatment is performed at a temperature of 700℃-800℃ for a time of 4-7 hours.

8. The application of the high-temperature titanium alloy according to any one of claims 1-4 in aero-engine parts, characterized in that, The aero-engine parts are bladed disks, blades, and turbine disks.

Citation Information

Patent Citations

  • Preparation method of high-strength 650 DEG C high-temperature titanium alloy large-size blisk forging

    CN115007775A

  • Titanium alloy resistant to high temperature of 700 DEG C for aero-engine and preparation method of titanium alloy

    CN116770130A

  • Heat resistant titanium alloy

    JP1997165634A